2018
DOI: 10.1161/hypertensionaha.118.10862
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment of Arterial Hypertension in Children and Adolescents

Abstract: Pharmacological treatment is indicated in children and adolescents with hypertension unresponsive to lifestyle modifications, but there is not enough evidence to recommend 1 class of antihypertensive drugs over others. We performed a network meta-analysis to compare the results of available randomized clinical trials on pharmacological treatment of pediatric hypertension. From a total of 554 potentially relevant studies, 13 randomized placebo-controlled clinical trials enrolling ≥50 patients and a follow-up ≥4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…Estudos conduzidos pela Organização Mundial de Saúde (OMS) projetam que, em 2025, haverá 75 milhões de crianças obesas ao redor do mundo, fator que, somado a outros fatores genéticos e ambientais, pode desencadear a expressão de níveis pressóricos elevados. Adicionalmente, dados recentes da Europa demonstram que os números de casos de HA aumentam ainda mais entre crianças com sobrepeso ou obesidade, alcançando um índice de 22% de prevalência (Burrello et al, 2018).…”
Section: Resultsunclassified
“…Estudos conduzidos pela Organização Mundial de Saúde (OMS) projetam que, em 2025, haverá 75 milhões de crianças obesas ao redor do mundo, fator que, somado a outros fatores genéticos e ambientais, pode desencadear a expressão de níveis pressóricos elevados. Adicionalmente, dados recentes da Europa demonstram que os números de casos de HA aumentam ainda mais entre crianças com sobrepeso ou obesidade, alcançando um índice de 22% de prevalência (Burrello et al, 2018).…”
Section: Resultsunclassified
“…[31] It is effective in reducing blood pressure and beneficial in protecting heart function, with few reported side effects. [32] Dobson et al [26] reported that the most commonly prescribed drug class was ACEIs, followed by β-receptor blockers, CCBs, and α-receptor blockers in US children aged 2 to 18 years. Yoon et al [33] and Binka et al [34] found that ACEIs were the most frequently prescribed monotherapy for adolescents in the US.…”
Section: Discussionmentioning
confidence: 99%
“…First-line treatment, especially in obese, is lifestyle intervention with salt restriction and weight loss. Pharmacological treatment is indicated in hypertensive children unresponsive to lifestyle modifications, as well as in children with symptomatic hypertension, secondary hypertension, target organ damage, diabetes mellitus or chronic kidney disease [17,18]. Antihypertensive treatment is started with the lowest dose of a single drug and titrated if needed until maximum recommended dose is reached.…”
Section: Hypertensionmentioning
confidence: 99%
“…If blood pressure is still elevated, the second drug can be added and up-titrated. The choice of particular antihypertensive drug is partly dependent on underlying etiology, partly on other relevant factors, such as end organ damage, concurrent disorders, side effects and clinician's preference [17,18].…”
Section: Hypertensionmentioning
confidence: 99%